1992
DOI: 10.1083/jcb.119.1.239
|View full text |Cite
|
Sign up to set email alerts
|

Activation-dependent changes in human platelet PECAM-1: phosphorylation, cytoskeletal association, and surface membrane redistribution.

Abstract: Abstract. PECAM-1 is a recently described member of the immunoglobulin gene (Ig) superfamily that is expressed on the surface on platelets, several leukocyte subsets, and at the endothelial cell intercellular junction. Recent studies have shown that the extracellular domain of PECAM-1, which is comprised of 6 Ig-like homology units, participates in mediating cell-cell adhesion, plays a role in initiating endothelial cell contact, and may later serve to stabilize the endothelial cell monolayer. PECAM-1 also has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 53 publications
(78 reference statements)
3
62
1
Order By: Relevance
“…It has been reported that the reorganization of actin cytoskeleton (stress fiber formation), and redistribution of a group of endothelial cell tight junction proteins from the TX-100-soluble to the TX-100-insoluble fractions are associated with transendothelial permeability in brain endothelial cells [32]. Triton-insoluble cytoskeleton is largely composed of F-actin filament and PE-CAM-1 is associated with both the Triton insoluble and soluble cytoskeleton and its distribution depends on the activation state of the cell [33]. For example, during thrombin-induced platelet aggregation, PECAM-1 partitions with the Triton-insoluble cytoskeleton increased from 10% to 60% of total cellular PECAM-1 [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the reorganization of actin cytoskeleton (stress fiber formation), and redistribution of a group of endothelial cell tight junction proteins from the TX-100-soluble to the TX-100-insoluble fractions are associated with transendothelial permeability in brain endothelial cells [32]. Triton-insoluble cytoskeleton is largely composed of F-actin filament and PE-CAM-1 is associated with both the Triton insoluble and soluble cytoskeleton and its distribution depends on the activation state of the cell [33]. For example, during thrombin-induced platelet aggregation, PECAM-1 partitions with the Triton-insoluble cytoskeleton increased from 10% to 60% of total cellular PECAM-1 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Triton-insoluble cytoskeleton is largely composed of F-actin filament and PE-CAM-1 is associated with both the Triton insoluble and soluble cytoskeleton and its distribution depends on the activation state of the cell [33]. For example, during thrombin-induced platelet aggregation, PECAM-1 partitions with the Triton-insoluble cytoskeleton increased from 10% to 60% of total cellular PECAM-1 [33]. In confluent endothelial cells, 20% to 30% of PECAM-1 was found associated with the cytoskeleton [31,34] and it increased to 65% during cell migration [31].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the roles of PECAM-1 and Flk-1 in allantoic vasculogenesis are not known, it is thought that PECAM-1 is involved in endothelial cell survival and migration (Gao et al, 2003;Newman, 1999;Newman and Newman, 2003), and is differentially localized to the cell surface in migratory endothelial cells and intercellular junctions in nonmigrating cells (Gratzinger et al, 2003;Newman et al, 1992;Wong et al, 2000). That PECAM-1 is found on the surface of allantoic cells suggests that it is required for cell survival.…”
Section: Vascularization Of the Allantois (Lb-onwards; ∼ ‡75 Dpc)mentioning
confidence: 99%
“…Immunohistochemical (IHC) studies demonstrated that CD31 is distributed diffusely on the surfaces of inflammatory cells and platelets (Ohto et al 1985;Metzelaar et al 1991;Bogen et al 1992;Newman et al 1992). However, initial light microscopic studies of cultured endothelial cells in vitro and of the vasculature in vivo reported that CD31 was concentrated at the lateral borders of endothelial cells, i.e., at sites of interendothelial cell contact (Muller et al 1989(Muller et al ,1993Albelda et al 1990;Metzelaar et al 1991;Vaporciyan et al 1993;Ayalon et al 1994;Carlos and Harlan 1994;Newman 1994Newman ,1997Zocchi et al 1996).…”
mentioning
confidence: 99%